Liberalism and enlightened political economy - Cardoso, José Luís (2015)
The emergence and development of political economy in the Age of Enlightenment is a complex process that shows the richness of a new science able to explain the functioning of a commercial society. The roots of political economy in the philosophical traditions of natural law help to explain its individual and liberal elements, but also its further implications for the development of the notions of human sociability, the common good, public happiness, and the betterment of society. The convergence of these different elements is crucial for understanding the common features of the variety of approaches belonging to the broad categorisation of enlightened political economy.Enlightenment,